2013
DOI: 10.3139/146.110943
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpies of mixing in liquid alloys of iron with the lanthanides

Abstract: The enthalpies of mixing in binary liquid alloys of iron with the lanthanides (Pr, Nd, Gd, Tb, Dy and Lu) were determined at 1550–1950 K by means of isoperibolic calorimetry. They show exothermic effects (in the Fe–Pr system partially endothermic) which increase across the lanthanides row from the Fe–Pr system (ΔHmin = −0.35 ± 0.10 kJ · mol−1 at xPr = 0.22; ΔHmax = 0.75 ± 0.24 kJ · mol−1 at xPr = 0.76; T = 1829 K) to the Fe–Lu system (ΔHmin = −11.58 ± 0.50 kJ · mol−1 at xLu = 0.35; T = 1950 K).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 14 publications
(17 reference statements)
1
18
0
Order By: Relevance
“…It is rather unusual to have minima of enthalpy of mixing where no solid compound exists. In addition, the results of Ivanov et al [52] are consistent with the systematic trend of enthalpy of mixing of all other binary liquid Fe-RE solutions, which will be discussed later in section 4. Therefore, the present model parameters of liquid solution were optimized to reproduce the more recent enthalpy data by Ivanov et al [52] in Fig.…”
Section: The Fe-gd (Iron-gadolinium) Systemsupporting
confidence: 78%
See 4 more Smart Citations
“…It is rather unusual to have minima of enthalpy of mixing where no solid compound exists. In addition, the results of Ivanov et al [52] are consistent with the systematic trend of enthalpy of mixing of all other binary liquid Fe-RE solutions, which will be discussed later in section 4. Therefore, the present model parameters of liquid solution were optimized to reproduce the more recent enthalpy data by Ivanov et al [52] in Fig.…”
Section: The Fe-gd (Iron-gadolinium) Systemsupporting
confidence: 78%
“…[34] The Gibbs energies of bcc Ho and fcc RE elements were taken from the FactSage FTLite database [15] hcp Gd solution was also needed to reproduce the rapidly increasing solubility of Fe in hcp Gd solution by Savitskii et al [46] The integral and the partial enthalpy of mixing of the Fe-Gd liquid were reported by Nikolaenko and Nosova [51] at 1850 K and Ivanov et al [52] at 1833 K as presented in Fig. 2.…”
Section: The Fe-gd (Iron-gadolinium) Systemmentioning
confidence: 99%
See 3 more Smart Citations